The production of capitalist "smooth" space in global port operations. (July 2015) - Wilmsmeier, Gordon; Monios, Jason
Highlights: Examines prevailing conceptualisations of space in port geography. Builds on the "spatial fix" concept drawn from Marx and Harvey. Develops the case for "smooth space" introduced by Deleuze and Guattari. Ports are socially constructed, contingent and, in many cases, contested spaces. Outlines the first steps of a critique of their capitalist context. Abstract: New developments in a post-Fordist economic environment have changed the source of port competitiveness from economies of scale based on basic production factors (capital, land, labour) to economies of scope based on advanced production (service) factors. The institutional setting in which ports are now embedded requires methods of analysis that go beyond those traditionally applied in transport geography, but port geography research has not embraced critical, radical or relational geographies. Thus, questions relating to the new conceptions of space and networks created through the corporatisation of the industry remain unanswered. This paper examines prevailing conceptualisations of space in port geography and elaborates the case for a smooth space conceptualisation. In doing so, it draws on two theoretical traditions of the spatial impacts of capital accumulation, beginning with Marx and Harvey to demonstrate how ports represent an exemplar of the inherently unstable "spatial fix" of mobile capital, then turning to the concept of "smooth space" introduced by Deleuze and Guattari. Using these concepts, the paper reflects on the production of capitalist smooth space in the global port operations sector, in which a handful of multinational corporations manage portfolios of major ports across the globe. The result is an inherent contradiction between a port's embeddedness in its local setting and regional hinterland and the expanding global corporatocracy driving its operational strategy. This paper argues, therefore, that port devolution and development cannot be understood in the absence of a critique of their capitalist context.